Development of a shelf- stable refrigerated chicken luncheon meat from mechanically recovered poultry meat - Masangkay, Carmencita S. (2002)
ABSTRACT The development of a highly acceptable refrigerated chicken luncheon meat from mechanically recovered poultry meat (MRPM) made shelf-stable by the incorporation of two antimicrobials was the main concern of this study. Descriptions for the sensory characteristics of highly acceptable chicken luncheon meat were gathered through Focus Group Discussion (FGD) sessions and were utilized in developing the MRPM-based chicken luncheon meat. To further economize and reduce the level of fat, the chosen formulation was substituted with varying levels of TSP, for part of the chicken meat. The sensory properties of the samples with 10, 20, and 30% TSP were not significantly different from each other. The sample with 20% TSP, having been accorded most desirable by the 50 panelists, was chosen for antimicrobial incorporation. In terms of the sensory properties, the samples with antimicrobials were not significantly different from the samples without. The microbiological analysis showed that the samples with antimicrobials had less microbial population than the control. The attributes of the chicken luncheon meat developed in this study closely match the FGD-derived descriptions for a highly acceptable chicken luncheon meat - having a sweet, spicy and salty flavor, compact and smooth texture, firm but tender mouthfeel.